2018
DOI: 10.1002/jca.21670
|View full text |Cite
|
Sign up to set email alerts
|

Granulomonocytapheresis as a cell‐dependent treatment option for patients with inflammatory bowel disease: Concepts and clinical features for better therapeutic outcomes

Abstract: Ulcerative colitis (UC) and Crohn's disease (CD) are major phenotypes of the chronic inflammatory bowel disease (IBD), which afflicts millions of individuals throughout the world with debilitating symptoms. The chronic nature of IBD means that patients require life‐long medications, and this may lead to drug dependency, loss of response together with adverse side effects as additional morbidity factors. The efficacy of antitumour necrosis factor (TNF)‐α biologics has validated the role of inflammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 94 publications
1
31
0
Order By: Relevance
“…GMA was performed with the Adacolumn (JIMRO Co., Ltd., Takasaki City, Japan) which contains cellulose acetate beads as leukocytapheresis carriers for myeloid lineage leukocytes . Each patient received up to 10 GMA sessions, at one, two, or three sessions per week.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GMA was performed with the Adacolumn (JIMRO Co., Ltd., Takasaki City, Japan) which contains cellulose acetate beads as leukocytapheresis carriers for myeloid lineage leukocytes . Each patient received up to 10 GMA sessions, at one, two, or three sessions per week.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, in Japan as well as in the European countries, GMA is favored by patients for its safety profile as well as for being a nonpharmacologic strategy for treating patients with active UC. The primary action of GMA for inducing anti‐inflammatory effect is to selectively deplete elevated granulocytes and monocyte as blood passes through the column . GMA initiates generation of regulatory B and T cells , which are the key requirements for a normal immune function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized, double‐blind, sham‐controlled clinical trial, granulocyte‐monocyte apheresis (GMA) did not demonstrate statistically significant differences in terms of clinical response, endoscopic remission, or quality of life as compared to placebo . Nonetheless, further data from observational studies have shown higher response rates, with better results in steroid‐dependent UC with a short disease duration . Recently, it has been suggested that the combination of GMA and anti‐tumor necrosis factor (TNF)‐alfa agents could regain the response in patients with LOR to these drugs .…”
Section: Introductionmentioning
confidence: 99%
“…5 Nonetheless, further data from observational studies have shown higher response rates, with better results in steroid-dependent UC with a short disease duration. 6 Recently, it has been suggested that the combination of GMA and anti-tumor necrosis factor (TNF)-alfa agents could regain the response in patients with LOR to these drugs. 7 The evidence of this potential approach with VDZ has also been described as a feasible option in this clinical situation, but the evidence comes only from case reports.…”
Section: Introductionmentioning
confidence: 99%